Consumo de frutas e hortaliças entre adultos nas capitais brasileiras e Distrito Federal, 2008-2016 - Luiza Eunice Sa da Silva (2018)
Introduction: Fruits and vegetables (F&V) are indispensable items in healthy diets. Their high nutritional content assigns them recognized health protection effect. However, it is known that in spite of the innumerable evidences indicating the health benefits of adequate F&V consumption, this is still achieved by a small share of the population. Objective: To identify the profile and temporal trend of fruit and vegetable consumption among adults in Brazilian capitals and Federal District (FD), between 2008 and 2016. Methods: Data from 463,817 adults interviewed by Vigitel (Surveillance System for Risk and Protective Factors for Chronic Diseases trough Telephone Interview) between 2008 and 2016. The distribution of the weekly frequency and the daily intensity of consumption of fruits and vegetables were estimated for each year for the entire studied population. Correspondence Analysis was used to verify the response profile of consumption evolving the weekly frequency and daily intensity of consumption of fruits and vegetables. After that, it was estimated the annual prevalence of regular (5days/week) and recommended (5x/day) consumption of fruits and vegetables, both for the complete set of the population and according to sex, age group, schooling level, municipality and region of residence. Prais-Winsten regression models were used to identify significant trends in the temporal variation of the indicators. Results: There was an increase in the weekly frequency of consumption of fruits and vegetables, as well as in the intensity of consumption of both groups. The analysis of consumption profile revealed that both the weekly frequency and the daily intensity of consumption of the food groups are related. The high weekly frequency or daily intensity of consumption of one of the groups (eg vegetables) tend to indicate similar scenario of consumption of the underlying group (eg fruits). There was also a significant increase in both the percentage of regular consumption of fruits and vegetables - from 33.0% to 35.2% - and of recommended consumption - from 20.0% to 24.4%. Similar increases are found in both sexes, most of the age groups, in educational levels and regions of the country. Conclusion: Similar consumption profiles evolving fruits and vegetables in adults in the state capitals and FD were identified, as well as a significant increase in the percentage of regular and recommended consumption of these groups. However, 3 out of 4 individuals continue to consume less F&V than recommended, reinforcing the need for new healthy eating promotion actions.